2021
DOI: 10.14744/eej.2021.86580
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of vascular endothelial growth factor A and its receptors in dental pulp of immature and mature teeth

Abstract: Objective: Vascular endothelial growth factor A (VEGFA) and its receptors are essential proteins for the angiogenic activity of dental pulp. Angiogenesis fundamentally provides oxygen and nutrients to cells for root formation and defence mechanisms. The angiogenic potential of dental pulp should be understood and considered for the conservative and regenerative endodontics. The purpose of this research was to measure the VEGFA expression and its receptors such as vascular endothelial growth factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…According to some studies, DPSCs could secrete the VEGF to improve the survival of endothelial cells to promote angiogenesis 32,33 . Meanwhile, there was a study that suggested that dental pulp tissue contained a high concentration of VEGF, which provided a significant contribution to the reparative response of the pulp tissues 34 . Furthermore, DPSCs could upregulate NG2 and play a role as the pericyte‐like cells to form vascular networks 35,36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to some studies, DPSCs could secrete the VEGF to improve the survival of endothelial cells to promote angiogenesis 32,33 . Meanwhile, there was a study that suggested that dental pulp tissue contained a high concentration of VEGF, which provided a significant contribution to the reparative response of the pulp tissues 34 . Furthermore, DPSCs could upregulate NG2 and play a role as the pericyte‐like cells to form vascular networks 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“… 32 , 33 Meanwhile, there was a study that suggested that dental pulp tissue contained a high concentration of VEGF, which provided a significant contribution to the reparative response of the pulp tissues. 34 Furthermore, DPSCs could upregulate NG2 and play a role as the pericyte‐like cells to form vascular networks. 35 , 36 As a result, we concluded that DPSCs possessed the capability to promote the repair and regeneration of oviduct injuries by promoting angiogenesis.…”
Section: Discussionmentioning
confidence: 99%